Implementation of Problem-Based Learning Model by Speak and Draw Techniques to Improve the Students’ Understanding Ability on the Explanation Text - Fitri Marlina Mulyani (International Journal of Multi Discipline Science, 2019)
This study aims to improve the students’ understanding ability on the explanation text after being implemented a problem-based learning model by speak and draw techniques. This study was a classroom action research that was composed of two cycles, each cycle consisting of four stages, namely the planning stage, the implementation of the action stage, the observation stage, and the reflection stage. This study was conducted on students of class XI MIPA7 on the 2nd semester of the academic year 2018/2019 in SMA Negeri 1 Wirosari, Wirosari District, Grobogan. The data collection technique was done through observation, questionnaires, and tests. The data collection instrument was done by using observation sheets, documentation, and a written test. The validity of this study was done by using content validity and construct validity. The results showed that the implementation of the Problem-Based Learning model by Speak And Draw techniques can improve the students’ understanding ability on the explanation text with the average value of students’ daily test who complete in Cycle I was 72.19 into 81.81 in Cycle II. The completeness percentage of the average value in Cycle I was 69% into 94% in Cycle II.